2022
DOI: 10.21603/2308-4057-2022-1-97-105
|View full text |Cite
|
Sign up to set email alerts
|

Improving the nutritional properties of Brassica L. vegetables by spontaneous fermentation

Abstract: Introduction. Brassica L. vegetables are rich in fiber, minerals, and bioactive compounds. Lactic fermentation can improve their nutritional value. The goal of this study was to evaluate phytase, calcium, phytic acid, total phenolic content, and antioxidants during spontaneous fermentation of white cabbage, red cabbage, and Chinese cabbage. Study objects and methods. The research featured samples of water extract, methanol extract, and brine. The procedure involved monitoring lactic bacteria and pH durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The DPPH antioxidant activity of raw and pickled cabbages is 9.68 and 9.33 mg TE/100 g (P > 0.05), respectively, and no change is observed after the brining process, similar to results reported in the literature (Girgin et al, 2015). Differently, in a previous research, the DPPH antioxidant activity of white cabbage increased on day 1 and then lowered through fermentation, probably due to the passage of antioxidant compounds to the brine (Parada et al, 2022). After in vitro digestion, DPPH antioxidant activity is found to remain unaffected by in vitro digestion of raw and pickled cabbage.…”
Section: Abts Dpph and Frap Antioxidant Activitysupporting
confidence: 87%
See 1 more Smart Citation
“…The DPPH antioxidant activity of raw and pickled cabbages is 9.68 and 9.33 mg TE/100 g (P > 0.05), respectively, and no change is observed after the brining process, similar to results reported in the literature (Girgin et al, 2015). Differently, in a previous research, the DPPH antioxidant activity of white cabbage increased on day 1 and then lowered through fermentation, probably due to the passage of antioxidant compounds to the brine (Parada et al, 2022). After in vitro digestion, DPPH antioxidant activity is found to remain unaffected by in vitro digestion of raw and pickled cabbage.…”
Section: Abts Dpph and Frap Antioxidant Activitysupporting
confidence: 87%
“…In a previous study (Sayın et al, 2015), the fermentation process was found to increase TPC initially and then decrease the TPC of white cabbage. In another spontaneous fermentation study, fermentation decreased the TPC of white cabbage (Parada et al, 2022). Sauerkraut production was found to increase TPC and some individual phenolics (Ciska et al, 2005a;Tlais et al, 2022).…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…The TFC increase was 55% in ST, 95% in TP, 70% in TT and 25% in JZ as compared to their respective raw samples. Although peculiar, such increase in the concentrations of bioactive compounds have also been reported in carrots, 41 daikon radish and red cabbage ferment mix, 42 dried g fruit juice fermented using LAB culture, 43 in individually fermented red, white and Chinese cabbage with 3% salt at 18 °C for 30 days, 21 and in market pickled commercial chayote. 25 Moreover, Irakoze et al (2023) reported such increase in fermented African Black Nightshade and African Spider Plant.…”
Section: Total Phenolics and Avonoid Contentsmentioning
confidence: 87%
“…Brining also helps in the preservation of nutrients and antioxidant compounds. 20,21 Such basic processing techniques ensure the 'organic status' of WEVs, promoting good health and well-being of the consumers. Besides, they show potential to boost the economic livelihoods of the forestdwelling tribal populations, fostering holistic sustainable communities.…”
Section: Introductionmentioning
confidence: 99%